Penerapan Metode Analitycal Hierarchy Process-Simple Additive Weighting (AHP-SAW) dalam Penentuan Varietas Padi yang Unggul - Dona Adittia; Nurul Hidayat; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Rice (Oryza sativa L.) is a very important food crop in the world after wheat and corn. During the development of agricultural research appeared several varieties of rice. Variety itself is one important component that has a major contribution in increasing production and income of rice farming. Therefore, it takes a computer system to help farmers decide the varieties that will be planted in accordance with the environmental conditions of planting by considering some aspects of the criteria. In the design using Analytic Hierarchy Process - Simple Additive Weighting in order to give consideration / advice to farmers to determine the superior varieties. The result of this method is the rank of the varieties. Method AHP function to determine the value of the vector of weight of some rise varieties that criteria then made reference in is the rank of the varieties produced by the process SAW. In this research, the test is done by measuring the accuracy level with the result reaching accuracy above 80%. So the system that is created by using the method AHP-SAW can be applied as a supporting decision making in determining superior rice varieties.